2014
DOI: 10.5433/1679-0359.2014v35n6p3355
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile and cholesterol in meat cuts of ewe lambs fed different levels of concentrate

Abstract: Consumers are more interested in having healthier and better quality products. The diet offered to animals can strongly affect the composition of meat. Thus, this study aimed to evaluate the effect of different levels of concentrate on lipid profile (in natura meat) and cholesterol content (in natura and cooked meat) of ewe lambs' meat cuts. Therefore, twenty-four lambs with a mean weight of 23.1 ± 2.1 kg were confined and fed different levels of a concentrate (20, 40, 60 and 80%) for 120 days. The diets consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Values of desirable fatty acids (DFA) in the lamb meat reported by Madruga et al (2008), Coutinho et al (2014) and Costa et al (2015) ranged from 67 % to 84 % and were lower than the value observed in the present study (95 %). The DFA, which has been suggested as an indicator of dietary risk for cardiovascular disease, was useful when assessing meat quality (Costa et al, 2015).…”
Section: Fatty Acid Profile Levels Of Replacementcontrasting
confidence: 95%
See 2 more Smart Citations
“…Values of desirable fatty acids (DFA) in the lamb meat reported by Madruga et al (2008), Coutinho et al (2014) and Costa et al (2015) ranged from 67 % to 84 % and were lower than the value observed in the present study (95 %). The DFA, which has been suggested as an indicator of dietary risk for cardiovascular disease, was useful when assessing meat quality (Costa et al, 2015).…”
Section: Fatty Acid Profile Levels Of Replacementcontrasting
confidence: 95%
“…The lamb meat of the different treatments showed low values of UFA:SFA, characterized by a lower concentration of UFA. Coutinho et al (2014) obtained higher values of UFA:SFA (1.01) due to a higher percentage of UFA in the different meat cuts. The average of PUFA:S-FA was less than the minimum value (0.4) recommended value by the World Health Organization (2003).…”
Section: Fatty Acid Profile Levels Of Replacementmentioning
confidence: 87%
See 1 more Smart Citation
“…The Pesquisa Nacional de Saúde (Instituto Brasileiro de Geografia e Estatística [IBGE], 2014) revealed that 37% of the interviewed Brazilians regularly consumed red meat and chicken containing an excess of low-quality fatty tissues, wich is related to the development of NCDs (IBGE, 2014;Claro et al, 2015). From this perspective, there are studies that seek to elaborate, improve, and evaluate some foods with a focus on healthiness (Coutinho et al, 2014;L. A. Oliveira, Reis, Santana, Santos, & Carvalho, 2017;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a proven reservoir for essential micronutrients and several bioactive lipids (Shingfield et al, 2013). On the other hand, meat is a main source of fat in the diet and particularly Saturated Fatty Acids (SFA), (Coutinho et al, 2014) which have been related to the recent spreading of several diseases in humans, such as Cardiovascular Diseases (CVDs), obesity, diabetes, cancer, neurological and skin damages (Makkar and Beever, 2013;Savoini et al, 2016;Hilmia et al, 2017;Temple, 2018). Atherosclerotic complications are primarily responsible for elevated morbidity and mortality in many people around the world (Mansour and Ajeel, 2013).…”
Section: Introductionmentioning
confidence: 99%